(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Vision of the Semantic Web is to add meaning into the current web so machines can understand its contents. For the semantic web to succeed, it needs to take advantage of the existing web. New technologies have emerged to bridge the gap between current web and semantic web: microformats, RDFa and microdata. These technologies allow web page authors to embed extra semantic information within XHTML to mark up the structure. So when a given application accesses this semantic content, it will be able to tell more about the web page. Such a web page is readable by both human and machine. This paper describes these technologies with appropriate examples. It also explores their strength and weaknesses. Finally future considerations are illustrated. Â Keywords: RDFa, microformat, microdata, smantic markup, annotation